Offensive performance in soccer through lag sequential analysis: The case of a team in the Spanish second division - Diaz Diaz, A.; Ramos Verde, E. J.; Garcia Mano, J M.; Valverde Esteve, T (Journal of Human Sport & Exercise, 2018)
We evaluated the attacking play of a Spanish Second Division-A soccer team (10 league matches). The observational method of Lag Sequential Analysis was used, with exhaustive mutually exclusive categories based on set criteria. From a retrospective perspective, mean length values were detected for the patterns of the LW, RMIF and GK players (max-lag = -3) ; short for LMIF (max-lag= -1), LI and LC (max-lag = -2) and long for FOR (max-lag = -5) and LB, RC and RW (max-lag= -4). The prospective perspective revealed mean lengths for RB, RC and CI (max-lag = 3) and short for GK, RMFI and FOR (max-lag = 2). The long patterns correspond to the SSTR, RW, LW and LB players (max-lag =4) and MCI (max-lag =5). The greater relationships between players, in both perspectives, were generated between the full-backs (RB and LB) and the wingers on their side (RW and LW). Forthe centre-backs (RC and LC), the priority relationships are with the other defensive players on their team. The midfielders (RMIF and LMIF) did not show any bifurcations, complementing each other, since when one acts in the retrospective perspective, his partner does so in prospective. It was observed that the chances of winning grow as the number of shots at goal increases, or the chances of losing decrease. We confirm that Lag Sequential Analysis provides detailed, useful information about attacking play in soccer.